Incidental Findings of Papillary Carcinoma in Thyroid Observing patients of Previously Operated Clinical Specimens of Multinodular Goiter - Ifrah Zafar, Afra Samad, Amber Haroon, Aneeqa Naz, Nudrat Fayyaz, Aqsa Bukhari (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Papillary carcinoma is one of the common malignancy among all thyroid malignancies and constitutes about 57-75%. In most of cases this lesion is an incidental finding in biopsies specimens operated for MNG. But the incidence of papillary carcinoma in the setting of various thyroid disorders including MNG remains unclear. Hence, we conducted a study of five years from 2017 till 2021 to address this question. Aim: To rule out the incidence of Papillary Thyroid Carcinoma (PTC) especially associated connection with MNG Methodology: From retrospective study carried out in the pathology department of Ibne-Sina Hospital, Multan, the date of 631 cases of thyroid carcinomas were retrieved. All the patients underwent different thyroid surgeries. Data regarding the age, gender, clinical diagnosis as well as pathological diagnosis was recorded and results were analyzed on SPSS 25. Results: We reviewed 631 cases of thyroid and included in the analysis. Overall, n=558 cases were operated with clinical diagnosis of MNG. Among them, 54(10%) cases were reported as papillary carcinoma on the basis of histopathological examination. Conclusions: Incidentally discovered papillary thyroid carcinomas are more commonly identified in surgical specimens from cases with MNG. These findings highlighted the high risk of malignancy in MNG emphasizing on the fact that the carcinoma should never be underestimated as majority of these patients were presented with clinically diagnosis of MNG. Keywords: MNG, papillary thyroid carcinoma, malignancy